The Penetrated Male - Kemp, Jonathan (punctum books, 2013)
Through nuanced readings of a handful of modernist texts (Baudelaire, Huysmans, Wilde, Genet, Joyce, and Schreber's Memoirs), this book explores and interrogates the figure of the penetrated male body, developing the concept of the behind as a site of both fascination and fear. Deconstructing the penetrated male body and the genderisation of its representation, The Penetrated Male offers new understandings of passivity, suggesting that the modern masculine subject is predicated on a penetrability it must always disavow. Arguing that representation is the embodiment of erotic thought, it is an important contribution to queer theory and our understandings of gendered bodies.